CONTEMPORARY CHALLENGES BEFORE THE PARK FACILITY IN THE CITY OF SOFIA - Veselin Rangelov (World Science, 2023)
On June 27, 2023, an Ordinance was adopted amending and supplementing the Ordinance on the construction, maintenance and protection of the green system of the Metropolitan Municipality. Unfortunately, the general impression in the professional community is that a rare chance to synchronize the regulatory framework in line with globally established practices was wasted. the adopted changes in the regulation significantly deepen the problems of the green system in the city of Sofia and distance the urban development of the capital from world practice.